Exploration of the experiences of working stressors and coping strategies associated with menstrual symptoms among nurses with shifting schedules: a Q methodology investigation - Shu-Chuan Yu; Hsiao-Pei Hsu; Jong-Long Guo; Shu-Fen Chen; Shu-He Huang; Yin-Chen Chen; Chiu-Mieh Huang (BMC, 2021)
Abstract Background The essence and workload of nursing can easily lead to burdens associated with female nurses' menstrual symptoms, and consequently, result in decreased working performance. Without effective support this can lead to resignation due to maladaptation. This study adopted Q methodology to explore the experience of working stressors and coping strategies associated with menstrual symptoms among nurses with shifting schedules. Methods Data were collected in two stages. First, in-depth interviews were conducted to collect nurses' experiences. Sentences that best fit the study's purpose were extracted for the construction of Q statements. Second, nurses were allowed to subjectively rank these Q statements by using Q-sorts. A total of 90 participants ranked the designed Q statements. The Q factor analysis revealed a five-factor solution that accounted for 48.90% of the total variance. Results The five evident factors included: menstrual symptoms interfering in collaboration with colleagues, deficiency of professional function and stress due to symptoms burden, diverse experiences without a clear pattern, adapted self-management with and without medication use, and stress due to symptoms burden and using medication for self-management. Conclusions The identification of these five groups may facilitate the development of responsive strategies to meet nurses' preferences. Furthermore, identifying workplace factors that are associated with the adverse effects of menstrual symptoms on nurses will be helpful for nursing supervisors and hospital managers. Additionally, strategies that can be implemented to create supportive work environments are discussed.